Stochastic modeling of coalbed gas content: A case from Harcourt gas field of Bowen Basin, Australia. Issue 16 (18th August 2019) - Duan, Lijiang; Qu, Liangchao; Xia, Zhaohui; Zhang, Ming; Liu, Lingli; Zheng, Kening
ABSTRACT: A new method to build a stochastic model of as-received coalbed gas content was proposed, and the workflow is explained in detail in this paper. First, dry-ash-free gas content model was obtained by combining the trend property and residual property to reflect the main control factor of depth and inherent heterogeneity of coal seams. Second, ash model was converted from logging density model with relative density as an intermediate variable for overcoming the shortage of core data. Third, moisture model was built. Finally, the model of as-received gas content was obtained by a simple arithmetic conversion. This method was applied in Harcourt coalbed gas field of Bowen Basin, Australia, with a satisfactory result.